Challenges of Knowledge: Information Selection - Catalin Vasile Iordache; Constanta Popescu (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics)
Awareness represents both a necessity and a challenge. First and foremost, it is essential to familiarize the general public with the mechanisms and tools needed to address current risks. Additionally, it is crucial for experts to promote awareness in a consistent and accessible manner for all segments of the population. Only through close community collaboration we can prevent many of the issues we face today. Although the internet, social media, and artificial intelligence offer numerous benefits and make our lives easier, they have a significant impact on our choices and the way we think. However, not everything created or shared online is intended to inform us accurately or improve our well-being. There are malicious actors who distort the true purpose of the internet and social networks to promote their own agendas by spreading false information and disinformation.